Dietary intervention for tertiary prevention in head and neck squamous cell carcinoma survivors: clinical and translational results of a randomized phase II trial - Cavalieri, Stefano; Bruno, Eleonora; Serafini, Mara Serena; Lenoci, Deborah; Canevari, Silvana; Lopez-Perez, Laura; Hernandez, Liss; Mariani, Luigi; Miceli, Rosalba; Gavazzi, Cecilia; Pasanisi, Patrizia; Rosso, Elena; et al. (Frontiers in Oncology, 2024)
Background: There is a strong need for preventive approaches to reduce the incidence of recurrence, second cancers, and late toxicities in head and neck squamous cell carcinoma (HNSCC) survivors. We conducted a randomized controlled trial (RCT) to assess a dietary intervention as a non-expensive and non-toxic method of tertiary prevention in HNSCC survivors. Methods: Eligible participants were disease-free HNSCC patients in follow-up after curative treatments. Subjects were randomized 1:1 to receive a highly monitored dietary intervention plus Word Cancer Research Fund/American Institute for Cancer Research (AICR/WCRF) recommendations for cancer prevention (intervention arm) or standard-of-care recommendations (control arm). The planned sample size for the event-free survival evaluation (primary endpoint) was not reached, and the protocol was amended in order to investigate the clinical (nutritional and quality of life questionnaires) and translational study (plasma circulating food-related miRNAs) as main endpoints, the results of which are reported herein. Results: Hundred patients were screened, 94 were randomized, 89 were eligible for ITT analysis. Median EFS was not reached in both arms. After 18 months, nutritional questionnaires showed a significant increase in Recommended Foods Score (p=0.04) in the intervention arm vs. control arm. The frequency of patients with and without a clinically meaningful deterioration or improvement of the C30 global health status in the two study arms was similar. Food-derived circulating miRNAs were identified in plasma samples at baseline, with a significant difference among Countries. Conclusions: This RCT represented the first proof-of-principle study indicating the feasibility of a clinical study based on nutritional and lifestyle interventions in HNSCC survivors. Subjects receiving specific counseling increased the consumption of recommended foods but no relevant changes in quality of life were recorded between the two study arms. Food-derived plasma miRNA might be considered promising circulating dietary biomarkers.